The impact of tax structure on investment : an empirical assessment for OECD countries - Alves, José (2018)
In the present empirical analysis we try to assess the impact of taxation on investment growth. In particular, and by using gross fixed capital formation as a proxy for investment, we intend to evaluate the impact of the taxation structure in investment dynamics, in a short and a long-run perspectives. This empirical exercise was conducted for all OECD countries, during the 1980-2015 period. Through panel data econometric techniques, we find optimal tax-investment threshold values, specially higher for short-term than for long-term evolution. Also, we find optimal income taxation rounding 9%, in percentage of GDP, an average optimal value 12.7% for consumption taxes to promote annual investment growth.